2014
DOI: 10.1021/nl403596b
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved X-ray Diffraction Investigation of the Modified Phonon Dispersion in InSb Nanowires

Abstract: The modified phonon dispersion is of importance for understanding the origin of the reduced heat conductivity in nanowires. We have measured the phonon dispersion for 50 nm diameter InSb (111) nanowires using time-resolved X-ray diffraction. By comparing the sound speed of the bulk (3880 m/s) and that of a classical thin rod (3600 m/s) to our measurement (2880 m/s), we conclude that the origin of the reduced sound speed and thereby to the reduced heat conductivity is that the C44 elastic constant is reduced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…In contrast, for proteins, the data analysis aims to extract only largescale changes of global conformation, mainly because of the inherently limited spatial resolution of TRXL. Although a variety of large systems, such as metal nanoparticles (13,14), nanowires (15), metal thin films (16), and DNAs (17), have also been studied using time-resolved X-ray diffraction, only studies on small molecules and proteins are covered in this review (see Figure 1).…”
Section: Trxssmentioning
confidence: 99%
“…In contrast, for proteins, the data analysis aims to extract only largescale changes of global conformation, mainly because of the inherently limited spatial resolution of TRXL. Although a variety of large systems, such as metal nanoparticles (13,14), nanowires (15), metal thin films (16), and DNAs (17), have also been studied using time-resolved X-ray diffraction, only studies on small molecules and proteins are covered in this review (see Figure 1).…”
Section: Trxssmentioning
confidence: 99%
“…In fact, there are experimental reports focusing on the changes in the phonon group velocity. 55,56 Kwon et al 2 showed that silicon and germanium nanostructures have certain critical values of thickness where the phonon transport phenomena drastically change into the confinement regime. Cuffe et al 55 observed phonon dispersion modification in sub-30-nm-thick Si nanofilms.…”
Section: Resultsmentioning
confidence: 99%
“…Cuffe et al 55 observed phonon dispersion modification in sub-30-nm-thick Si nanofilms. Jurgilaitis et al 56 measured phonon dispersion in 50-nm-thick InSb nanowires using time-resolved XRD and found that the speed of sound is only 74% of that in the bulk counterpart. They also found that the elastic constant was reduced by 35% compared to the bulk value.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrafast phenomena in materials can be excited by optical pulses with durations of femtoseconds to picoseconds, an excellent match for the characteristic timescales of processes relevant to materials processing and fundamental physical phenomena. Time-resolved x-ray diffraction methods enable the study of the physics of condensed matter systems, including ultrafast laser-induced lattice dynamics of oxide materials, [1][2][3][4] semiconductor lattice dynamics, 5,6 and the metal-insulator transition in VO 2 . 7 Several physical mechanisms result in the coupling of optical excitation to structural phenomena.…”
Section: Introductionmentioning
confidence: 99%